Customer Prefrency Analysis in The Design of Traditional Fruit Retail Smees in Bojonegoro - Moh. Saiful Anam; Edi Suhartono (Enrichment : Journal of Management, 2020)
The decision of consumers to choose products in traditional fruit retail SMEs is not only based on one attribute, such as price or brand. They see a product as a whole, namely by looking at the combination of features and attributes that exist. After seeing the combination of features and attributes of the existing product, the buyer is faced with a trade-off situation before making a decision. On the other hand, a traditional fruit retail SME must understand consumer desires for the products they will sell. The above problems can be overcome by using the Conjoint Analysis method. This method can be used to understand consumer preferences and perceptions. The results obtained from this method are the relative importance level of the attributes and level of fruit and packaging products chosen by consumers, marketing segmentation, and the relative importance of the technical response of traditional fruit retail SMEs in Bojonegoro. With this method, the company can design product packaging according to the attributes and level of consumer choice that are tailored to the technical capabilities of a traditional SME.